An Examination of the Use of the Framework of Social Marketing to Achieve Environmental Sustainability in International Agricultural and Extension Education - Laura A. Warner; Theresa Pesl Murphrey (Journal of International Agricultural and Extension Education, 2015)
An integrated literature review was conducted to describe a technique for promoting environmentally sustainable behavior change and encourage discussion and use of this approach among international extension educators across the globe. Campaigns from several countries which incorporated varying elements of social marketing were examined using a structured framework that included: audience segmentation; research-based analysis of an audience’s perceptions toward the behavior; the articulation of specific, measurable behavioral goals; and the use of social marketing tools and other principles (e.g., social norms, messaging, commitment, incentives/disincentives, prompts and reminders, and a participatory approach). Consideration for human behavior was lacking in the majority of campaigns, and many could have increased their impact by incorporating additional social marketing elements. A second stage of the literature review was conducted to illustrate the social marketing principles and tools that made up the framework. The first stage included the examination of nine environmental behavior change campaigns, while the second stage integrated an additional 30 resources. It was determined that there is a gap in the literature documenting social marketing practices being used to encourage environmentally sustainable behavior change around the globe. A call is made for increased education and documentation of the elements of social marketing to encourage environmental sustainability
Keywords: Behavior change; extension strategies; international extension; sustainability; social marketing